Cardiopulmonary resuscitation quality and beyond: the need to improve real-time feedback and physiologic monitoring. Issue 1 (December 2016) - Lin, Steve; Scales, Damon
Abstract High-quality cardiopulmonary resuscitation (CPR) has been shown to improve survival outcomes after cardiac arrest. The current standard in studies evaluating CPR quality is to measure CPR process measures—for example, chest compression rate, depth, and fraction. Published studies evaluating CPR feedback devices have yielded mixed results. Newer approaches that seek to optimize CPR by measuring physiological endpoints during the resuscitation may lead to individualized patient care and improved patient outcomes.